OFR-72-79 Feasibility Of Longwall Mining In Non-Fossil Fuel Deposits. - Kenneth Wardell (The National Institute for Occupational Safety and Health (NIOSH), 1978)
Those flat lying, bedded or replacement, non-fossil fuel deposits which exist within the U.S.A., and which are amenable to longwall mining, are identified by reference to three principal factors associated with their physical/geological environments. These are their depth, extent and structural continuity. Technical feasibility is assessed in relation to the likely cutting speeds which can be achieved in the identified minerals with existing longwall shearer machines. Economic comparisons are made between traditional mining operations in those deposits for which technical feasibility is demonstrable. Continents are made concerning those technical deficiencies which appear to preclude the application of existing longwall equipment to the identified deposits and suggestions are made regarding the lines of research aimed at improving longwall technology.